Rodzina wobec poszkodowanego w wypadku jej członka - Florek, Magdalena (Wydawnictwo Naukowe UAM, 2005)
An accident is an event which primarily causes many negative effects in its direct victim, but which also has a destructive influence on the way the families of the victims function. The factors that cause the negative effects stem from the limited performance of social roles and family roles, as well as from material losses, and stress. It is uplifting that for the majority of the injured, the family have showed up to be a support group, explicitly performing their caretaking role.
The family facing one of their members falling victim to an accident